2018
DOI: 10.1109/lsp.2018.2861212
|View full text |Cite
|
Sign up to set email alerts
|

Light Field Denoising via Anisotropic Parallax Analysis in a CNN Framework

Abstract: Light field (LF) cameras provide perspective information of scenes by taking directional measurements of the focusing light rays. The raw outputs are usually dark with additive camera noise, which impedes subsequent processing and applications. We propose a novel LF denoising framework based on anisotropic parallax analysis (APA). Two convolutional neural networks are jointly designed for the task: first, the structural parallax synthesis network predicts the parallax details for the entire LF based on a set o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…To further evaluate the preservation of the light field parallax structure quantitatively, we compared the light field parallax edge precision-reall (PR) curves (Chen, Hou, and Chau 2018) of the angularly super-resolved light fields, and Fig. 6 shows the results.…”
Section: Resultsmentioning
confidence: 99%
“…To further evaluate the preservation of the light field parallax structure quantitatively, we compared the light field parallax edge precision-reall (PR) curves (Chen, Hou, and Chau 2018) of the angularly super-resolved light fields, and Fig. 6 shows the results.…”
Section: Resultsmentioning
confidence: 99%
“…Single view NLM [8] BM3D [9,10] SGN [11] Real image denoising [12] Universal denoising networks [13] FFDNet [14] Video VBM3D [15] VBM5D [16] With optical flow estimation [17] Frame-to-frame training [18] SALT [19] Multi-view NLM with PS [20] With occlusion handling [21] MVCNN [22] LFBM5D [24,25] APA [26] An epipolar plane image (EPI) is a typical means of expressing the structure of multiviews. In an EPI, the relative motion between cameras or objects is expressed as lines that have different slopes depending on the depth.…”
Section: Target Applications Denoising Algorithmsmentioning
confidence: 99%
“…LFBM5D has also been applied to remove artifacts in super resolution studies of LF images [ 25 ]. Furthermore, Chen et al used a CNN to remove noise from LF images based on an anisotropic parallax analysis (APA) [ 26 ]. For real-time LF denoising, 4-dimensional (4D) linear and shift-invariant hyper fan filters have been proposed and implemented in hardware [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the application of a deep neural network to multi-view denoising has attracted researchers’ attention. Chen et al [39] proposed a light field denoising framework based on anisotropic parallax analysis. In this work, two convolutional neural networks (CNN) will jointly predict parallax information and restore non-Lambertian variations to each view.…”
Section: Related Workmentioning
confidence: 99%
“…This method, though simple and convenient, does not exploit the redundant image information that exists in multiple views capturing the same scene. Numerous studies [32,33,34,35,36,37,38,39,40,41,42,43,44] have demonstrated that inter-view redundant information is essential for recovering the original image details without creating undesirable over-smoothing artifacts that are common in single image denoising. Therefore, we believe that the denoising performance of CNN model can be further enhanced if inter-view information, in addition to intra-view information, is taken into consideration.…”
Section: The Proposed Denoising Networkmentioning
confidence: 99%